Clinical analysis of 30 cases of patients with nutcracker syndrome complicated with IgA nephropathy - WANG Ming-jun; SONG Ya-shan (Linchuang shenzangbing zazhi)
Objective To analyze the clinical features of nutcracker syndrome complicated with IgA nephropathy, so as to improve the accuracy of diagnosis and efficiency of treatment. Methods Thirty cases of patients with nutcracker syndrome complicated with IgA nephropathy were designated as group I; 90 cases of adult patients with IgA nephropathy without nutcracker syndrome, who had undergone left renal vein Doppler examination, as group II; and 60 cases of patients with single nutcracker syndrome as group III. Clinical, laboratory, imaging and pathological data of patients in the three groups were analyzed retrospectively. Results The ratio of male to female in group I was 1∶3.29, which showed that females were significantly more than males. The body mass index in groupⅠand Ⅲ were lower than group Ⅱ. The hypo-C3-emia rate in group I was 56.7%, higher than that in group II(P<0.01). The inner diameter at the left renal vein site with stenosis with groupⅠand Ⅲ was evidently narrower than that with groupⅡ(P<0.01). Conclusions It’s recommended that, those adult patients with long-term nutcracker syndrome with hypo-C3-emia should undergo renal biopsy for a definitive diagnosis; and left renal vein Doppler ultrasonic examination should be taken into account for those slim female adults with IgA nephropathy with decreased serum C3 level.